Pengaruh Penyuluhan Manfaat Jus Wortel Untuk Mengatasi Dismenore Pada Remaja Putri Di Smp Swasta Al-Ihsan Mulia - Utary Dwi Listiarini; Nurrahmaton; Nur Lisma (Awatara Publisher, 2024)
Dysmenorrhea or menstrual pain usually occurs during menstruation. Reducing the level of dysmenorrhoea pain with one non-pharmacological method using traditional medicine is carrots. This research was to determine the effect of counseling on the benefits of carrot juice on dysmenorrhoea in young women. This research uses a Quasi Experimental method with a one group pretest-posttest design. The population in this study was all 22 class IX students of Al-Ihsan Mulia Private Middle School, Medan Helvetia District, Medan City. The sampling technique is to use the total population. Data analysis uses univariate analysis and bivariate analysis with the Dependent T Test (Paired Sample T Test). Research shows that knowledge in the pre-test of female students with good knowledge was 3 people (13.6%), sufficient knowledge was 13 people (59.1%) and 6 people had poor knowledge (27.3%) while knowledge in the post-test There were 19 female students with good knowledge (86.4%) and 3 students with sufficient knowledge (13.6%). The results of the bivariate test show the Sig value. (2-tailed) of 0.000 < 0.05.There is an influence of counseling about the benefits of carrot juice on dysmenorrhoea in young women on the knowledge of Class IX female students at Al-Ihsan Mulia Private Middle School, Medan Helvetia District, Medan City. It is recommended for young women to be more active in searching for appropriate information in the media. information about dysmenorrhea and non-pharmacological treatment methods as well as the benefits of carrot juice for dysmenorrhoea.